2015
DOI: 10.1016/j.bjorl.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral changes in individuals undergoing hematopoietic stem cell transplantation

Abstract: Mucositis accounted for the increased score and potential risk of clinical complications. Gingivitis, ulcers, and pericoronitis were other changes identified as potential risk factors for clinical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
3
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 26 publications
1
19
3
13
Order By: Relevance
“…Our study cannot thoroughly confirm this previous finding. Likewise, a couple of studies with a 100‐day follow‐up did not notice any changes in DMFT index or an increase in new dental caries lesions in this short follow‐up period . However, in this study, hyposalivation was observed to be associated with progression towards a higher DMFT index score.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Our study cannot thoroughly confirm this previous finding. Likewise, a couple of studies with a 100‐day follow‐up did not notice any changes in DMFT index or an increase in new dental caries lesions in this short follow‐up period . However, in this study, hyposalivation was observed to be associated with progression towards a higher DMFT index score.…”
Section: Discussioncontrasting
confidence: 54%
“…Likewise, a couple of studies with a 100-day follow-up did not notice any changes in DMFT index or an increase in new dental caries lesions in this short follow-up period. 15,36 However, in this study, hyposalivation was observed to be associated with progression to- hypotheses and many previous studies where hyposalivation has been observed as a risk factor for oral diseases that may eventually lead to tooth loss and expensive oral rehabilitation. Additionally, caries prevalence was observed to be consistently higher in HSCT recipients with hyposalivation at all study time points, but the results were not statistically significant, except for HSCT recipients with hyposalivation pre-HSCT.…”
Section: Stimulated Saliva Flow Rates and Associations Of Hyposalivcontrasting
confidence: 56%
See 1 more Smart Citation
“…Hastalarda 2. ve 3. değerlendirmede immun supresyonda alınan ilaç toksisitesiyle ilişkili olarak oral mukozit yaygın görülmüştür. (10) Allojenik kök hücre transplantasyonu yapılan myeloid lösemi tanılı 48 hasta ile yapılan yarı deneysel çalışmada, Busulfan (3 gün busulfan, FB3) tedavisi alan hastalarda (n=27) Mephalan (FM140) tedavisi alan hastalara (n=21) göre istatistiksel olarak anlamlı bir şekilde (p=0.013) daha şiddetli stomatit görülmüştür. (11) Otolog kök hücre transplantasyonu öncesi yüksek doz kemoterapi alan multiple myelom (MM) ve non hodking lenfoma (NHL) tanılı hastalarda oral mukozit insidansı, süresi, mukozit şiddetini etkileyen etkenler transplantasyondan 30 gün sonrasına kadar değerlendirilmiştir.…”
Section: öZunclassified
“…If it remains there, it can irritate the gum and lead to pericorinitis 8 . If the pericorinitis is severe overlooked, the swelling & infection may extend beyond the jaw to the check and neck 9,10 .…”
Section: Introductionmentioning
confidence: 99%